Formative and Summative Assessment in the Light of Students Perceptions - Chughtai, Mohammad Ali; Khalid, Mariya; Afridi, Saira; Shah, Syed Nasir (Journal of Gandhara Medical and Dental Science, 2017)
OBJECTIVES To collect information about the Perceptions of dental students regarding Formative and Summative Assessment in Sardar Begum Dental College. METHODS This cross sectional study was conducted at Sardar Begum Dental College, Peshawar. Pre validated Assessment Experience Questionnaire was used to collect information. All the students of 2nd, 3rd, 4th year BDS and House officers who have joined and continued their bachelors education at Sardar Begum Dental College and Hospital from the first year were invited to participate in this study through Convenience sampling technique after taking verbal and written consent. RESULTS Overall response rate was 29.3% in 2nd Year, 35.1% in 3rd year, 75.7% in 4th Year and 92.7% among house officers.60-70% students opined that formative assessment experiences stimulated deep learning and were useful in the preparation for summative assessment. Majority of the students were satisfied with the atmosphere, structure and conduct of summative assessment. More than 70% admitted that they learn more when preparing for summative assessment near the examination. Almost 60% prefer to have more number of SEQs by claiming that these let them apply deep learning. Despite of accepting the contents of OSCE/OSPE as of good quality, majority students from all the professional years were dissatisfied from the time allocation as well as slides and images placed in each station CONCLUSION Students like formative assessment mainly because of feedback as it helps them in learning as well as preparing for summative assessment. All parts of summative assessment were more satisfactory for the students.